Changes in Antarctic Ice Sheet Motion Derived From Satellite Radar Interferometry Between 1995 and 2022 - Rignot, Eric; Mouginot, Jeremie; Scheuchl, Bernd; Jeong, Seongsu (Geophysical research letters, 2022)
Ice motion and boundaries are critical information for ice sheet models that project ice evolution in a warming climate. We present four historical, continent‐wide, maps of Antarctic‐wide ice motion and boundaries for the time period 1995–2022. The results reveal no change in the interior region of East Antarctica, iceberg detachments at ice shelf fronts, and widespread glacier speedup that propagates 100 km's inland in West Antarctica and the Antarctic Peninsula. Speedup affects the entire drainage of the Amundsen Sea Embayment sector; the entire west coast of the Antarctic Peninsula down to GeorgeVI Ice Shelf; the east coast down to Larsen C Ice Shelf; Getz Ice Shelf, Hull and Land glaciers in West Antarctica; Matusevitch, Ninnis, Mertz and Denman glaciers, glaciers in Porpoise and Vincennes Bay; and Robert, Wilma and Rayner glaciers in Enderby Land, in East Antarctica. We attribute the observed glacier changes to increased melting by warmer ocean waters. Plain Language Summary Ice velocity is a fundamental variable of glacier evolution that governs the transfer of mass from the ice sheets to the ocean. It is best measured from satellite platforms but long time series require combination of multiple satellite data of various performance levels and incomplete spatial coverage. We assembled the first set of continent‐wide mosaics using 2–5 years of data in each period to maximize spatial coverage and detect changes in ice dynamics over the entire continent. The results reveal no signal over most of the interior but important changes at the coast concentrated along channels occupied by outlet glaciers. In the Amundsen Sea Embayment sector of West Antarctica, changes are pervasive over the entire drainage, which indicates that the coastal forcing from the ocean affects the entire ice sheet. The products reveal precise areas of rapid change in the West and East coasts of the Antarctica Peninsula, and in West and East Antarctica. These observations will help constrain ice sheet models in charge of reconstructing ice sheet past changes and projecting its evolution in a changing climate. Key Points We present historical, continent‐wide, mosaics of Antarctic ice motion using a suite of satellite sensors spanning 28 years We report areas of accelerated flow stretching over 100 km's from the coast and the entire drainage of the Amundsen Sea Embayment sector The observed, ongoing, detailed glacier changes will help constrain ice sheet numerical models in charge of reconstruction and projection